Practice regarding menstrual hygiene among reproductive age group in Myagang rural municipality 2, Nuwakot. - Pokharel,Melina (2020)
ABSTRACT: Background Reproductive women age group has been recognized as a special period in life cycle. This period is marked with transition phase of childhood to adulthood with starting of menarche. It is linked with several perceptions and practices, which sometimes results in adverse health outcomes. So, this study was carried out to assess practices of menstruation in reproductive women age group.To find out its related problems practices. Methods: A descriptive cross sectional study was carried out during JanuaryAugust 2019 in myagang gaupalika 2 bungtang nuwakot.Using simple random sampling method with 126 sample size. Results: In this study Sanitary pad were used by 77(61.1)% women. And 73.8% women were using water to clean genitals during menstruation. Restriction from worship was high (82.5%).cleaning pubic area during pad changing in menstruation is 90.5%. and 32.5% women were bath daily and also good practices is 118(93.7) and poor practice is 8(6.3) . Conclusions: Abdominal pain was main PMS.And they are going for treatment is using homemade treatment then health facility.practices of menstruation is satisfied. And also there is good practice is satisfactory. Keywords: Reproductive Menstruation, Menarche, Premenstrual symptom, Sanitary Napkin, Absenteeism